Per1/Per2 double knockout transcriptome analysis reveals circadian regulation of hepatic lipid metabolism - Yiran Bu; Si Chen; Mengcheng Ruan; Libang Wu; Hualin Wang; Na Li; Xiuju Zhao; Xiaoli Yu; Zhiguo Liu (Food Science and Human Wellness)
Scope: Circadian disorder and high-fat diet (HFD) can disturb lipid metabolism homeostasis and may promote the development of various metabolic diseases. The relationship between them is of great concern. This study aimed to explore the effects of Per1/Per2 double knockout (DKO) on hepatic lipid metabolism in mice under HFD and HFD with docosahexaenoic acid (DHA) substitution. Methods and results: Both wild type (WT) and DKO male C57BL/6 mice were fed with normal chow diet (CON), HFD, or HFD with DHA substitution (AO) for 15 weeks. At the end of the experiment, mice were sacrificed at zeitgeber time (ZT) 0 (7:00 am) or ZT12 (7:00 pm). Pathological indicators were determined using histological and biochemical methods. Hepatic transcriptome sequencing analysis showed that DKO mice exhibited multiple dysfunctions in diurnal rhythm, drug metabolism, cell cycle, cancer pathways, and lipid metabolism. HFD had greater effects on fatty acid oxidation and cholesterol synthesis and metabolism in Per1-/-Per2-/- mice, which was improved by DHA substitution. Conclusions: Per1/Per2 played an important role in the circadian regulation of hepatic lipid metabolism, and DKO mice were more sensitive to HFD. DHA can improve circadian-related lipid metabolism disruption induced by HFD in mice.